2017
DOI: 10.1016/j.chemosphere.2017.07.130
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic activity, chemical levels and health risk assessment of municipal distribution point water from Pretoria and Cape Town, South Africa

Abstract: Endocrine disrupting chemicals (EDCs) are ubiquitous in the environment and have been detected in drinking water from various countries. Although various water treatment processes can remove EDCs, chemicals can also migrate from pipes that transport water and contaminate drinking water. This study investigated the estrogenic activity in drinking water from various distribution points in Pretoria (City of Tshwane) (n = 40) and Cape Town (n = 40), South Africa, using the recombinant yeast estrogen screen (YES) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(29 citation statements)
references
References 64 publications
0
18
1
Order By: Relevance
“…In African Clawed Frog populations (Xenopus laevis), the presence of testicular ovarian follicles was observed in male frogs caught in the north-eastern region of South Africa, which are situated in areas of high agricultural pesticide usage (Du Preez et al, 2009). Male X. laevis frogs collected within impoundments in the Western Cape also situated near agricultural practices also showed modulation of testicular spermatogenic development and altered plasma steroid-and thyroid hormone levels (Van Wyk et al, 2014). As these studies only aimed to link the presence of endocrine disruption in wildlife to pesticide contamination in water systems, the presence of other contaminants, such as pharmaceuticals and personal care products (PPCPs) or synthetic steroid hormones was most probably overlooked.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In African Clawed Frog populations (Xenopus laevis), the presence of testicular ovarian follicles was observed in male frogs caught in the north-eastern region of South Africa, which are situated in areas of high agricultural pesticide usage (Du Preez et al, 2009). Male X. laevis frogs collected within impoundments in the Western Cape also situated near agricultural practices also showed modulation of testicular spermatogenic development and altered plasma steroid-and thyroid hormone levels (Van Wyk et al, 2014). As these studies only aimed to link the presence of endocrine disruption in wildlife to pesticide contamination in water systems, the presence of other contaminants, such as pharmaceuticals and personal care products (PPCPs) or synthetic steroid hormones was most probably overlooked.…”
mentioning
confidence: 99%
“…Although the harmful effects of man-made pollutants on wildlife species are well documented (Heath and Classen, 1999; Barnhoorn et al, 2004;Bornman et al, 2009;Wagenaar et al, 2012;Kruger et al, 2013;Van Wyk et al, 2014), no national monitoring programmes or water quality guidelines have been implemented in South Africa to assess and monitor the occurrence and frequency of pollutants affecting endocrine pathways of non-target organisms (Jooste, 2008). The clinical implications of EDC contamination in surface waters have also received little attention in South Africa, and the importance of using sentinel species as bio-indicators of water pollution is regularly overlooked, especially by assessing the health of these organisms up-and downstream of water treatment processes.…”
mentioning
confidence: 99%
“…This study demonstrated that the most responsive toxicity pathways were related to xenobiotic metabolism, modulation of hormone systems, reactivity, and adaptive stress responses. Although endocrine effects in this study were mainly induced by (treated) wastewater and storm water (residential run off), other studies demonstrated hormone system–related responses induced by drinking water (Conley et al ; Van Zijl et al ; Shi et al ). Both endocrine disruption and DNA reactivity may underlie carcinogenesis and be related to reproduction and developmental effects, health effects with considerable impact on quality of life (GBD 2016 DALYs and HALE Collaborators ).…”
Section: Selection Of Effect‐based Toolsmentioning
confidence: 61%
“…Data on the health effects of phthalates in Africa was also extremely limited-only three articles retrieved in our literature search evaluated the impact of exposure to phthalates and any health outcomes in an African study population (Colacino et al, 2011;Kumar et al, 2017;Van Zijl et al, 2017). Adverse health outcomes evaluated in these articles were preterm birth (Kumar et al, 2017) and estrogenic activity (Van Zijl et al, 2017). The third study focused on sources of exposure to phthalates among premenstrual girls in Egypt, reporting BMI, waist and hip circumference, and other anthropometric characteristics, comparing rural and urban study participants.…”
Section: Health Outcomesmentioning
confidence: 99%
“…Phthalates were measured in urine using enzymatic deconjugation of the metabolites from their glucuronidated form, solid-phase extraction, separation with high performance liquid chromatography, and detection by isotope-dilution tandem mass spectrometry as described previously (Silva et al, 2007;Van Zijl et al, 2017). Estrogenic activity was identified in drinking water from Pretoria and Cape Town that also contained detectable levels of estrogens, bisphenol-A, and phthalates.…”
Section: Exposures Measuredmentioning
confidence: 99%